2018
DOI: 10.1371/journal.pone.0192123
|View full text |Cite|
|
Sign up to set email alerts
|

Mouse IgG2c Fc loop residues promote greater receptor-binding affinity than mouse IgG2b or human IgG1

Abstract: The structures of non-human antibodies are largely unstudied despite the potential for the identification of alternative structural motifs and physical properties that will benefit a basic understanding of protein and immune system evolution as well as highlight unexplored motifs to improve therapeutic monoclonal antibody. Here we probe the structure and receptor-binding properties of the mouse IgG2c crystallizable fragment (Fc) to compare to mouse IgG2b and human IgG1 Fcs. Models of mIgG2c Fc determined by x-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 44 publications
(49 reference statements)
1
7
0
1
Order By: Relevance
“…Since these antibodies are capable to recognize membrane-associated NS1 dimers in ZIKV-infected cells, we expect that, under in vivo conditions, this would favor the clearance of infected cells. The presence of higher IgG2c levels in pgDNS1-ZIKV immunized AB6 mice also supports this hypothesis, since IgG2c antibodies are known to strongly bind to ADCC-mediator FcyRIV (67,68). Thus, the enhanced immunity observed in this group may be related to the role of gD on the modulation of the induced antigen-specific responses.…”
Section: Discussionsupporting
confidence: 58%
“…Since these antibodies are capable to recognize membrane-associated NS1 dimers in ZIKV-infected cells, we expect that, under in vivo conditions, this would favor the clearance of infected cells. The presence of higher IgG2c levels in pgDNS1-ZIKV immunized AB6 mice also supports this hypothesis, since IgG2c antibodies are known to strongly bind to ADCC-mediator FcyRIV (67,68). Thus, the enhanced immunity observed in this group may be related to the role of gD on the modulation of the induced antigen-specific responses.…”
Section: Discussionsupporting
confidence: 58%
“…It has also been shown that C H 2 loop motion and relative domain orientation influence the Fc−FcγR interaction in human and mice. 16,24 Interestingly, although the macaque IgG Fcs are very similar in their crystallographic structures and MmIgG1 shows the most structural similarity to HsIgG3, solution NMR spectroscopy detected the same or greater motion of the N 297 glycan among the MmIgG Fcs as observed for HsIgG1 Fc. In addition, MmIgG1 spectra exhibited GlcNAc 1 H1-C1 peak features most similar to that of HsIgG1.…”
Section: Discussionmentioning
confidence: 80%
“…23 Furthermore, the positions of comparable peaks from mouse IgG2b and 2c Fc also correlate with FcγRIV binding affinity. 24 Thus, this H 1 -C 1 correlation represents a well studied and valuable reporter of IgG Fc structure. The GlcNAc 1 H 1 -C 1 correlations appeared at comparable resonance frequencies for all IgG Fcs tested (Figure 5(a)).…”
Section: Mmigg1 Displays the Highest Structural Similarity To Hsigg3mentioning
confidence: 99%
“…The same analytical approach was applied to mouse IgG2b Fc and IgG2c Fc. Unlike human Fc, the mouse proteins showed only one peak for the Asn-linked N-acetylglucosamine residue; however, the peak from IgG2c Fc was found further to the right and mIgG2c bound mouse Fc γ receptor IV with ~5-fold greater affinity that mIgG2b Fc, consistent with the stabilized conformation observed in hIgG1 Fc (Falconer & Barb, 2018). …”
Section: Solution Nmr Of Labeled Glycoproteinsmentioning
confidence: 61%